Boost thermoelectric properties of n-type PbSe:Ag2Se:Ag in the vicinity of the percolation threshold. (February 2023) - Wang, Jinrong; Ning, Xingkun; Wang, Jia; Wang, Shufang
Abstract: We study the microstructure and thermoelectric performance of n -type (PbSe)100-x- y :(Ag2 Se) x :(Ag) y ( x = 0 − 6, y = 0–28) films. For the (PbSe)71 :(Ag2 Se)5 :(Ag)24, the carrier concentration enhanced in the vicinity of the percolation threshold. The high carrier concentration leads to a large average PF avg at the low temperature range of 300−523 K, the maximum PF avg for (PbSe)100-x- y :(Ag2 Se) x :(Ag) y samples is ∼37.83 μW cm −1 K −2, which is about 200% higher than that of pure PbSe films (∼19.16 μW cm −1 K −2 ). In addition, PbSe:Ag2 Se:Ag grain boundary and edge dislocation can engender intrinsically low thermal conductivity. The low thermal conductivity leads to a high zT and the maximum zT values for (PbSe)71 :(Ag2 Se)5 :(Ag)24 samples is ∼0.63 at room temperature, which is more than 250% higher than that of pure PbSe films ( zT = 0.25). Graphical abstract: A significant enhancement of thermoelectric performance in n -type (PbSe)100-x-y :(Ag2 Se)x :(Ag)y ( x = 0 − 6, y = 0–28) films was achieved at low temperature. For the (PbSe)71 :(Ag2 Se)5 :(Ag)24, the carrier concentration enhanced from 2.36 × 10 19 cm −3 to 7.45 × 10 19 cm −3 in the vicinity of the percolation threshold. The high carrier concentration leads to a large average PF avg at the low temperature range of 300−523 K, the maximum PF avg for (PbSe)100-x-y :(Ag2 Se)x :(Ag)y samples is ∼37.83 μW cm −1 K −2, which is about 200% higher than that of pure PbSe films (∼19.16 μW cm −1 K −2 ). Image, graphical abstract